Effects of Calcination Temperature on Photocatalytic Activity of WO3 Materials for Tetracycline Degradation in Aqueous Environment under Visible Light - Huong, Nguyen Thuy; Khoa, Nguyen Viet; Hanh, Nguyen Thi; Trang, Hoang Thu; Truong, Dang Quang; Cuong, Nguyen Chi; Anh, Nguyen Phuong Hoang; Quynh, Ngo Truc; Thao, Bui Thi Thu; Hoai, Nguyen Thi Thu; Dong, Pham Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 3DO - 10.25073/2588-1140/vnunst.5542, 2023)
In the research, we successfully investigated effects of calcination temperature on the characteristics and photocatalytic activities of WO 3 applying for degradation of antibiotics in aqueous environment under visible light. The crystal phases and optical properties of the synthesized WO 3 nanoparticles were determined by an X-ray diffractometer (XRD), an UV-VIS diffuse reflectance spectroscopy (UV-VIS) and a photoluminescence spectroscopy (PL). The photocatalytic activities of the WO 3 materials, which were calcinated at different temperatures, were studied via degradation of Tetracycline under visible light. Obtained results indicated that the orthorhombic phase was converted completely to monoclinic phase when the sample was calcinated at 500 o C. As compared to these WO 3 -300, WO 3 -400 and WO 3 -600 samples, the WO 3 -500 sample, which was calcinated at 500 o C, showed significant decrease in band gap energy and electron-hole recombination rate. Thus, the WO 3 -500 exhibited novel photocatalytic activity for Tetracycline degradation under visible light.